Precision measurement of single-electron current with quantized Hall array resistance and Josephson voltage. (28th October 2020) - Bae, Myung-Ho; Chae, Dong-Hun; Kim, Mun-Seog; Kim, Bum-Kyu; Park, Suk-In; Song, Jindong; Oe, Takehiko; Kaneko, Nobu-Hisa; Kim, Nam; Kim, Wan-Seop
Abstract: A single electron pump was incorporated with a quantum Hall resistance and a Josephson voltage for the current evaluation in the framework of Ohm's law. The pump current of about 60 pA level was amplified by a stable amplifier with a gain of 10 3 to induce a Hall voltage of about 60 mV level across a 1 MΩ Hall resistance array, which was compared with the Josephson voltage. The gain of the current amplifier was calibrated with a cryogenic current comparator bridge. For two different drive frequencies and repeated thermal cycles, the comparisons demonstrated that the pump current averaged over the first plateau was equal to ef within the combined uncertainty level of 0.3 × 10 −6 ( k = 1).